The Small Size and Superficial Location Suggest That Laparoscopic Partial Nephrectomy Is the First Choice for the Treatment of Juxtaglomerular Cell Tumors - Ye, Zixing; Fan, Hua; Tong, Anli; Xiao, Yu; Zhang, Yushi (Frontiers in Endocrinology, 2021)
Background: Juxtaglomerular cell tumor (JGCT) is a very rare disease, and surgical resection is the only possible way to cure this tumor. Open nephrectomy and partial nephrectomy have been reported to manage JGCTs with excellent results in the previous reviews. Laparoscopic surgery has been popularized in recent years, while critical issues associated with laparoscopic surgical management have been seldom reported. We summarized the JGCTs in our center to discover the optimal surgical management and its anatomic foundation. Methods: In this retrospective study, we enrolled a total of 14 JGCT patients. All patients received surgeries and were followed up for up to 11 years. We mainly summarized the size and location of tumors, imaging features, and surgical strategies. A descriptive statistical analysis was performed. Results: The JGCTs in this study had a median size of 1.35 cm and all located superficially, mainly in the cortical or subcortical area of the kidney. All 14 patients had hypertension, ten had hypokalemia, and seven had elevated plasma renin activity. Pathologically, JGCT cells were polygonal or spindle shape, with positive CD34 and vimentin immunostaining. All patients received partial nephrectomy; nine were laparoscopic, and five were open. Laparoscopic partial nephrectomy (LPN) was performed in seven out of eight patients over the last nine years. Postoperative blood pressure, serum potassium, and plasma renin activity were normal in all patients. No recurrence occurred within a median follow-up of 60 months. Conclusion: The small size and superficial location are the characteristic anatomic features of JGCT; they suggest that LPN is the preferred surgical strategy. Laparoscopic ultrasound is helpful for the intraoperative detection of small JGCTs. Longer follow-up is required to examine the biological behavior of JGCTs and the effect of LPN.